1989
DOI: 10.1063/1.101517
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and structure of epitaxial Er silicide films on (111) Si

Abstract: Thin metallic silicide films epitaxially grown on Si(111) and their role in Si-metal-Si devices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…The substrate contribution to the Si 2p spectra for these coverages .The Si(1 l l) 7x7 surface has a metallic character in which the Fermi level is stable at 0.65 eV above the valence band Fig.1-Si 2~ Vectra as a function maximum and thus the substate component for this surface ofErcoverage reconstruction can be used as reference [13]. Taking account for a value of the Si gap of 1.12 eV we found a SBH IZ)B = 0.29 f 0.05 eV for thick silicide layers ( above 2 Er monolayers) in agreement with values found in the litterature [3,5,12]. The SBH decreases down to a value = 0.13 f 0.05 eV for the 2D Er silicide.…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…The substrate contribution to the Si 2p spectra for these coverages .The Si(1 l l) 7x7 surface has a metallic character in which the Fermi level is stable at 0.65 eV above the valence band Fig.1-Si 2~ Vectra as a function maximum and thus the substate component for this surface ofErcoverage reconstruction can be used as reference [13]. Taking account for a value of the Si gap of 1.12 eV we found a SBH IZ)B = 0.29 f 0.05 eV for thick silicide layers ( above 2 Er monolayers) in agreement with values found in the litterature [3,5,12]. The SBH decreases down to a value = 0.13 f 0.05 eV for the 2D Er silicide.…”
Section: Methodssupporting
confidence: 74%
“…It crystallizes in the A1B2 structure with defects in the Si lattice giving rise to an average composition ErSi2-, (X = 0.3). Furthermore high crystalline quality silicide films can be grown epitaxially on Si(1 l l) with ErSiZX (0001) parallel to Si (11 1) [3-61. A 43x43 R30° superstructure is observed and commonly attributed to ordered arrays of Si vacancies [5].In this paper we report on Schottky barrier height (SBH) measurements and interface structure determination of a two-dimensional (20) erbium silicide layer epitaxially grown on n-type Si(ll1). As previously shown [7-91, this silicide layer can be prepared with a very high degree of cristallinity by annealing one Er monolayer deposited on Si (1 11) at room temperature and subsequently annealed in the 400 -600°C temperature range.…”
Section: Introductionmentioning
confidence: 99%
“…6 Erbium disilicides have the primitive cell parameters cϭ0.409 nm and aϭ0.378 nm giving rise to a Ϫ1.3% mismatch with the ͗111͘Si surface and good quality epitaxial thin films ͑ϳ10 nm͒ have been grown in UHV systems by codeposition at room temperature ͑RT͒ of Er and Si in the ratio 1:2 followed by annealing at a temperature between 700-900°C. 7 Even in this case the film was substoichiometric and it has been suggested that the Si vacancies form to release the compressive stress suffered by the silicon atoms which are arranged in hexagonal rings with a Si-Si distance of 0.218 nm 7 which is ϳ8% smaller than the corresponding one in the silicon lattice. Several authors have reported evidences of a regular deposition of the vacancies in the lattice.…”
mentioning
confidence: 93%
“…Several authors have reported evidences of a regular deposition of the vacancies in the lattice. [7][8][9] In this letter we will show that good quality epitaxial films of ErSi 2Ϫx can be grown on ͗111͘Si substrate by the reactive deposition technique provided that during deposition a convenient partial pressure of oxygen is maintained into the chamber so that ϳ7 at. % of O is incorporated into the film.…”
mentioning
confidence: 99%
“…1,2) In recent years, rare-earth (RE) metal silicides have attracted considerable attention, because they can lower the Schottky barrier height on an n-type silicon surface. [3][4][5] Consequently, the RE metal silicides are excellent candidate materials for fabricating infrared detectors.…”
Section: Introductionmentioning
confidence: 99%